PENGEMBANGAN KEWIRAUSAHAAN BERBASIS POTENSI LOKAL UNTUK MASYARAKAT PANTAI BALE BALE KOTA BATAM, KEPULAUAN RIAU - V Ade Arianto CP; Merline Julianti; Daris Purba; Nasruji; Elli Widia; Hendri Kremer (JURNAL PENGABDIAN MANDIRI, 2025)
Pantai Bale Bale Nongsa, located in Batam, Indonesia, has abundant local potential but faces challenges in optimizing its resources for sustainable development. This study aimed to enhance entrepreneurship through financial literacy, local product development, and digital marketing strategies for the community. A participatory descriptive approach involving surveys, training, and mentoring was employed. Results demonstrated significant improvements in financial literacy, local product diversification, and online marketing capabilities, leading to increased daily incomes for some micro-entrepreneurs. This program highlights the importance of integrating financial literacy, product innovation, and digital marketing to empower coastal communities sustainably.